Implementation of Science, Technology, and Society Approach in Science Learning to Develop Science Literacy: Evidence-Based Literature Review - Ana Zuyyina Ulfah; Zainul Arifin Imam Supardi; Erman Erman; Muhammad Satriawan; Iqbal Ainur Rizki (Jurnal Pendidikan Sains Indonesia, 2025)
The low level of students science literacy in Indonesia, as reflected in international assessments such as PISA, indicates that many students still struggle to understand and apply scientific concepts in real life contexts. This problem is often linked to the limited use of contextual and integrative learning approaches in science education. Therefore, this study aims to analyze the implementation of the STS approach to improve students' scientific literacy. The research method used is a SLR with a PRISMA design. Articles were collected from the google scholar database covering the years 2020 to 2025, and 20 studies met the inclusion and exclusion criteria. The results of the review indicate that the STS approach is effective in improving science literacy by strengthening students conceptual understanding, critical thinking, and environmental awareness through active learning methods and the integration of digital media. However, challenges such as limited teacher competence, lack of training, and insufficient learning resources hinder optimal implementation. Therefore, efforts to improve teacher professional development and develop contextual learning media are essential to maximize the success of STS based science learning